A numerical study of crack shielding/anti-shielding in layered architectures. (July 2019) - Lu, Songsong; Laborda, Andreu; Cook, Richard; Zhang, Yi; Verbickas, Rolandas; Reed, Philippa
Highlights: Shielding and its interactive effect with anti-shielding on crack tip field in multi-layered architectures. Establishing a method to predict the fatigue crack life in layered architectures considering the shielding/anti-shielding effect. In 4-layered architectures, the increase of first hard layer's thickness and the decrease of distance between first hard layer and the top surface will improve the fatigue performance. Abstract: Previous research has indicated the potential effectiveness of adopting micro-scale layered architectures to improve the fatigue damage resistance of coatings. However, the optimisation of these coatings is difficult due to the existence of many different factors affecting fatigue performance in such micro-scale layered architectures. In particular, the interaction of successive shielding and anti-shielding processes on crack growth resistance is therefore addressed in this paper by numerical simulation analysis. The crack tip fields in a series of layered architectures were simulated based on varying assumed constitutive materials properties to reveal the interaction of shielding/anti-shielding characteristics in complex architectures in a simple exemplar system. The evolution of crack driving force (CDF) with crack length was calculated and linked to fatigue crack life under relatively simple conditions, including straight crack path and Paris law assumptions, to investigate the effect of the ordering of shielding/anti-shielding characteristics on the crack tip field and hence on fatigue crack life. Layered architectures with different numbers, ordering and placing of layers, were assessed and parametric studies of 4 layered architectures were carried out. This allows analysis of the effect of these individual factors on shielding and their interactive effect with anti-shielding in multi-layered architectures. Understanding the combined effect on crack growth performance and overall fatigue life controlled by crack propagation provides insight into the generic design of micro-scale layered architectures.